STUDI KELAYAKAN BISNIS LE PETIT KIDS CAFÉ DI GADING SERPONG KABUPATEN TANGERANG - JULIANA .; CARROLINE . (JURNAL ILMIAH MAKSITEK, 2020)
Le Petit Kids Café is a place to sell food and drinks specifically for parents and their children. When they come to this café,parents can bring their children who are babies up to elementary school age, where these ages are the ages at which thechildren practice their motoric movements. Le Petit Kids Café will provide children's toys that can train children's motoricmovements, starting from mini slides, mini trampolines, as well as other toys that stimulate creativity such as legos, woodenblocks and other toys. So besides being a place for children to play and learn, this café also aims so that parents who comewith their children can rest and enjoy time at Le Petit Kids Café, while children are playing in the playground area, or evenbecome a place for family recreation. The purpose of this research is to analyze the feasibility of the Le Petit Kids Cafébusiness whether it is feasible to run or not. The research method used is descriptive research method. The data collectionprocess was carried out by distributing questionnaires to 317 respondents using convenience sampling techniques,observation, and interviews. The analysis method consisted of several aspects, namely analysis of market and marketingaspects, operational aspects, organizational and human resources aspects, and financial aspects. Le Petit Kids Café is aviable and profitable business.